2004
DOI: 10.1002/aoc.654
|View full text |Cite
|
Sign up to set email alerts
|

Separation of organic compounds binding trace elements in seeds of Leuzea carthamoides (Willd.) DC

Abstract: The distribution of trace elements into important groups of compounds in seeds was investigated using a seven-step sequential extraction of seed biomass (solvents used: petroleum ether, ethyl acetate, butanol, methanol, methanol +

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…nicotianamine and its derivatives) can also be considered as potential candidates for Cd transport in vascular tissues, and further from the phloem into embryonic tissues. Overall, the results of Cd coordination in seeds are consistent with previous studies where Cd was mainly found in thiolate-rich complexes in flaxseed (Lei et al 2003), and also bound to phytic acid (Pavlikova et al 2004). The presence of mixed sulfur (thiolate) and oxygen (phytate) ligands in seeds suggests that at least two routes of loading and storage of Cd exist in the seeds of T. praecox: the first one would involve transport and loading of Cd-thiolate complexes, and the second would mimic transport and loading of Zn, as proposed previously (Tauris et al 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…nicotianamine and its derivatives) can also be considered as potential candidates for Cd transport in vascular tissues, and further from the phloem into embryonic tissues. Overall, the results of Cd coordination in seeds are consistent with previous studies where Cd was mainly found in thiolate-rich complexes in flaxseed (Lei et al 2003), and also bound to phytic acid (Pavlikova et al 2004). The presence of mixed sulfur (thiolate) and oxygen (phytate) ligands in seeds suggests that at least two routes of loading and storage of Cd exist in the seeds of T. praecox: the first one would involve transport and loading of Cd-thiolate complexes, and the second would mimic transport and loading of Zn, as proposed previously (Tauris et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…The fractionation of soybean seeds has shown that Cd is mainly bound in soy whey (50%) and soy proteinate (32%) (Cataldo et al 1981). In flaxseed, Cd was mainly found in a thiol-rich protein fraction (Lei et al 2003) and in a 0.10 M protein fraction (Oomah et al 2007), while in the seeds of the medicinal plant Leuzea carthamoides, Cd was mainly in the methanol + H 2 O + HCl fraction (compounds isolated from cell walls and cytoskeleton after hydrolysis-phytic acid and its salts, and proteins) (Pavlikova et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 35% of ligands were formed by O-in the first shell, with P-in the second shell (Cd-O-P-coordination), implying a bond to phytate. Lei et al (2003) also determined Cd coordination in seeds of flax, where Cd was mainly associated with thiolate-rich complexes and also bound to phytic acid (Pavlikova et al 2004). The presence of mixed sulfur (thiolate) and oxygen (phytate) ligands in seeds suggests that at least two routes of loading and storage of Cd exist in the seeds of T. praecox: The first one would involve transport and loading of Cd-thiolate complexes, and the second would mimic transport and loading of Zn, as proposed previously (Tauris et al 2009).…”
Section: Coordination In Reproductive Tissuesmentioning
confidence: 99%
“…Increased inhibition of proline biosynthesis resulted in the preference of metabolic way of phytochelatin synthesis, glutamate kinase activity therefore decreased in As, Cd and Zn treatments of the pot experiment. According to our previous results of sequential extraction of spinach biomass (Pavlíková et al 2004(Pavlíková et al , 2005) the mass portion of phytochelatins fractions increased in spinach cultivated on soil contaminated with toxic elements as well as with sewage sludge. The role of proline accumulation in plants stressed by toxic elements has not been fully elucidated.…”
Section: Resultsmentioning
confidence: 73%